One‐Pot Synthesis and Formation Mechanism of Hollow ZSM‐51. Issue 24 (4th April 2019) - Zhang, Yunjuan; Che, Shunai
Abstract: Coffin‐shaped hollow ZSM‐5 zeolite (HZZ) particles with shell thickness of about 200 nm and hollow diameter of approximately 1.5 μm were synthesized in one pot by using tetrapropylammonium bromide (TPABr), aluminum triisopropoxide Al[OCH(CH3 )2 ]3 and tetraethoxysilane (TEOS) as the structure‐directing agent (SDA), aluminum and silica source, respectively. The appropriate molar ratios of TPABr/SiO2 and Si/Al as well as suitable crystallization temperature are the key factors for the formation of HZZ. The formation of the HZZ can be attributed to the existence of intrinsic density variation inside the initial amorphous aggregates and the Al zoning in the outer surface of the ZSM‐5 particles. Amorphous silica with low crystallinity formed at early stages and low Al concentration, which has been subsequently dissolved and recrystallized on the ZSM‐5 particle surface through Ostwald ripening, leading to the formation of HZZ. This approach, which uses a high concentration of SDA, will provide new possibilities and insight into the prospective fabrication of hollow zeolites. Abstract : Coffin‐shaped hollow ZSM‐5 zeolite (HZZ) particles with a shell thickness of approximately 200 nm and a hollow diameter of about 1.5 μm were synthesized in one pot by using highly concentrated tetrapropylammonium bromide (TPABr) as the structure‐directing agent.